Brain imaging of cognitively normal individuals with 2 parents affected by late-onset AD - Lisa Mosconi; John Murray; Wai Hon Tsui; Yi Li; Nicole Spector; Alexander Goldowsky; Steven Williams; Ricardo S. Osorio; Pauline McHugh; Lidia Glodzik; Shankar Vallabhajosula; Mony J. de Leon (2014)
This brain imaging study examines whether cognitively normal (NL) individuals with 2 parents affected by late-onset Alzheimer disease (LOAD) show evidence of more extensive Alzheimer disease pathology compared with those who have a single parent affected by LOAD.Fifty-two NL individuals received MRI, (11)C-Pittsburgh compound B (PiB)-PET, and (18)F-fluoro-2-deoxyglucose (FDG)-PET. These included 4 demographically balanced groups (n = 13/group, aged 32-72 years, 60% female, 30% APOE ε4 carriers) of NL individuals with maternal (FHm), paternal (FHp), and maternal and paternal (FHmp) family history of LOAD, and with negative family history (FH-). Statistical parametric mapping, voxel-based morphometry, and z-score mapping were used to compare MRI gray matter volumes (GMVs), partial volume-corrected PiB retention, and FDG metabolism across FH groups and vs FH-.NL FHmp showed more severe abnormalities in all 3 biomarkers vs the other groups regarding the number of regions affected and magnitude of impairment. PiB retention and hypometabolism were most pronounced in FHmp, intermediate in FHm, and lowest in FHp and FH-. GMV reductions were highest in FHmp and intermediate in FHm and FHp vs FH-. In all FH+ groups, amyloid-β deposition exceeded GMV loss and hypometabolism exceeded GMV loss (p < 0.001), while amyloid-β deposition exceeded hypometabolism in FHmp and FHp but not in FHm.These biomarker findings show a "LOAD parent-dose effect" in NL individuals several years, if not decades, before possible clinical symptoms.